1991
DOI: 10.1007/bf01973713
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of sodium dichromate depending on the route of administration

Abstract: A comparison of the effects of intraperitoneal and subcutaneous routes of administration of sodium dichromate on nephrotoxicity in rats was studied. Dichromate when injected subcutaneously (SC group) produced a higher degree of nephrotoxicity than when administered intraperitoneally (IP group). It caused severe progressive proteinuria followed by polyuria and glucosuria, reaching maximum levels at 3 days after treatment in the SC group, whereas it produced mild proteinuria without glucosuria in the IP group. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Pathological studies have shown that signs of early nephropathy caused by Cr compounds were located in the proximal tubular brush border (Evan and Dail 1974;Franchini et al 1978;Kirschbaum et al 1981). Renal injury has been reported in both human and rodents after dichromate administration (Kim and Na 1991). Acute tubular necrosis and renal failure caused by massive absorption of chromic acid has also been reported (Berndt 1976;Pedersen and Mørch 1978;Appenroth and Bräunlich 1988).…”
Section: Discussionmentioning
confidence: 94%
“…Pathological studies have shown that signs of early nephropathy caused by Cr compounds were located in the proximal tubular brush border (Evan and Dail 1974;Franchini et al 1978;Kirschbaum et al 1981). Renal injury has been reported in both human and rodents after dichromate administration (Kim and Na 1991). Acute tubular necrosis and renal failure caused by massive absorption of chromic acid has also been reported (Berndt 1976;Pedersen and Mørch 1978;Appenroth and Bräunlich 1988).…”
Section: Discussionmentioning
confidence: 94%
“…However, the toxic effects on cellular metabolism after Cr(VI) treatment of rats did not persist indefinitely, unlike the well-known metabolic inhibitors such as arsenic, cyanide, and mercury (Kim and Na 1990). In addition, metabolic disturbance has occurred with a lower dose (Kim and Na 1991 a) than the subthreshold doses of dichromate, which have been shown to have minimal effects on renal function (Christenson et al 1989). Therefore, it seems that the inhibitory effect of Cr(VI) on mitochondrial respiration may not be the major cause of Cr(VI)-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 97%
“…Chromium compounds are used commercially in industrial welding, metal finishes, leather tanning, and wood preservation [15]. The chromium ion is considered as one of heavy metals that are very essential for biochemical and physiological functions in plants and animals [16]. Although chromium is an essential micronutrient for the growth of many organisms, but at high concentration it is toxic, carcinogenic and cause allergic [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Although chromium is an essential micronutrient for the growth of many organisms, but at high concentration it is toxic, carcinogenic and cause allergic [17,18,19,20]. Potassium dichromate has many harmful and toxic effects on mammals and rats [16]. For example, toxic effects of potassium dichromate on sex hormones of female albino rats [21], respiratory cancers [17,22], and ototoxicity that cause a wide range of fetal effects [23].…”
Section: Introductionmentioning
confidence: 99%